EFEKTIVITAS KONSELING KELOMPOK CLIENT CENTERED UNTUK MENGEMBANGKAN PRESTASI BELAJAR SISWA KORBAN BROKEN HOME SMAN 2 SEMARANG - novira, riska selly; suhendri, suhendri; Mujiyono, Mujiyono (Jurnal Psikoedukasia, 2024)
The background that drives this research is the low learning achievement of students from Broken Home families. This is due to family conditions that do not support the process of student growth and development, causing children to show irresponsible behavior such as skipping class, smoking, pessimistic about the future, withdrawing from the social environment and even participating in brawls. This study aims to determine how effective client-centered group counseling is in developing the learning achievement of students who are victims of Broken Home. The research method used in this study is quantitative with the type of research true experimental design, with a control group design pre-test post-test model. In this study, the experiment process is divided into three stages, namely experiment preparation, experiment implementation, and the end of the experiment. This research instrument is a questionnaire of resilience level consisting of 41 statement items developed based on the Likert model scale preparation technique. The population in this study was class VIII of SMP N 39 Semarang which amounted to 324 students. Class XII MIPA 1 is the class used for validity and reliability testing with a Cronbach's Alpha value of 0.740 so that the instrument is declared reliable. The sample used was 14 Broken Home students who were taken using purposive sampling technique. The results of the t test calculation obtained sig value in the output table> 0.05. In the calculation of the Paired T test output, the sig. value is 0.604, so the results of the post-test data analysis calculation show that the average score of student learning achievement in the experimental group of 63.42 increased from and to 68.83 after treatment. In the experimental group there was an increase of 4.8. While in the group that was not given group counseling treatment, in fact there was only a minimal increase, from 66.83 to 67.50. In the control group there was an increase of 0.67. The difference between the experimental group and the control group is 4.13. Thus Ho is rejected and Ha is accepted so that there is an effectiveness of Client Centered Group Counseling to Develop Learning Achievement of Students Victims of Broken Home Sman 2 Semarang. Keywords: Learning Achievement of students, broken families, client centered group counselin